Hip and ankle range of motion and hip muscle strength in young female ballet dancers and controls. Issue 5 (1st October 1999) - Bennell, K; Khan, K M; Matthews, B; De Gruyter, M; Cook, E; Holzer, K; Wark, J D
Abstract : OBJECTIVES: To compare the hip and ankle range of motion and hip muscle strength in 8-11 year old novice female ballet dancers and controls. METHODS: Subjects were 77 dancers and 49 controls (mean (SD) age 9.6 (0.8) and 9.6 (0.7) years respectively). Supine right active hip external rotation (ER) and internal rotation (IR) were measured using an inclinometer. A turnout protractor was used to assess standing active turnout range. The measure of ER achieved from below the hip during turnout (non-hip ER) was calculated by subtracting hip ER range from turnout range, and hip ER:IR was derived by dividing ER range by IR range. Range of right weight bearing ankle dorsiflexion was measured in a standing lunge using two methods: the distance from the foot to the wall (in centimetres) and the angle of the shank to the vertical via an inclinometer (in degrees). Right calf muscle range was measured in weight bearing using an inclinometer. A manual muscle tester was used to assess right isometric hip flexor, internal rotator, external rotator, abductor, and adductor strength. RESULTS: Dancers had less ER (p<0.05) and IR (p<0.01) range than controls but greater ER:IR (p<0.01). Although there was no difference in turnout between groups, the dancers had greater non-hip ER. Dancers had greater range of ankle dorsiflexion than controls, measured in both centimetres (p<0.01) and degrees (p<0.05), but similar calf muscle range. After controlling for body weight, controls had stronger hip muscles than dancers except for hip abductor strength which was similar. Regression analyses disclosed a moderate relation between turnout and hip ER (r = 0.40). There were no significant correlations between range of motion and training years and weekly training hours. CONCLUSIONS: Longitudinal follow up will assist in determining whether or not hip and ankle range in young dancers is genetically fixed and unable to be improved with further balletic training.